Simulation of turbulent swirling multiphase flow inside a pressure -swirl atomizer using volume of fluid model [electronic resource] - Ahmadreza Abbasi Baharanchi, 1985-; Fakulti Kejuruteraan Mekanikal (2010)
Thesis (Sarjana Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2010